World Health Statistics 2011: How does Bangladesh compare with other South-East Asian countries? (South East Asia Journal of Public Health, 2013)
The World Health Statistics 2011 compiles the health and related data of its member states including a summary of the progress made towards achieving the health-related Millennium Development Goals (MDGs) and associated targets. This analysis examined data for Bangladesh and compares with the other ten member states of the WHO South-East Asia region. From the analysis, it is evident that considerable progress is being made to improve the health of the people of Bangladesh. Nevertheless, there remain many areas of concern over health development and provision of healthcare delivery and financing. In Bangladesh, annual population growth rate and adolescent fertility rate are higher than regional averages. Life expectancy and mortality rates are not impressive in comparison to other regional countries. Overall burden of cause-specific mortality and morbidity is higher; however reported cases of selected infectious diseases are lower than regional average. In terms of health service coverage, in one hand some real concerns were noted (e.g. poor antenatal coverage and availability of skilled health personnel etc.) and on the other hand some achievements were accomplished (e.g. vaccination of measles, DTP3 etc.). Increasing number of underweight children and smoking among male adults are also the key areas of concerns. Bangladesh ranks in the bottom quartile of healthcare spending in the region; the percentage of GDP allocation for health is 3.3% which is far below the level needed to scale up essential health interventions. The country has also relatively few healthcare personnel and hospital beds, and health inequality is observed in the provision of health care delivery which is most prominent in lower socio-economic groups. With regards to health-related MDGs, except child mortality, other target may not be met. Findings from these cross-national comparisons can inform national policy, highlight areas where Bangladesh could improve, and yield benchmarks for improved healthcare performance.DOI: http://dx.doi.org/10.3329/seajph.v1i1.13206 South East Asia Journal of Public Health 2011:1(1)